The Story of Academic Ranking of World Universities - Liu, Nian Cai (International Higher Education, 2009)
Conceived as a project to benchmark Chinese Universities, the Academic Ranking of World Universities ranks 1,200 institutions world wide. As international interest in rankings increases, efforts continue to improve and diversify this ranking system.